If a tree falls [videorecording (DVD)] : a story of the Earth Liberation Front - Curry, Marshall (Oscilloscope Laboratories, 2011)
The remarkable story of the rise and fall of the Earth Liberation Front, a radical environmental group that the FBI calls America's 'number one domestic terrorist threat,' told through the transformation and radicalization of one of its members, Daniel McGowan. Academy Award-nominated filmmaker Marshall Curry weaves a chronicle of McGowan facing life in prison with a dramatic investigation of the events that led to his involvement with the ELF.